2015
DOI: 10.1016/j.jhsa.2015.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Post-Acute Care Following Distal Radius Fracture Among Medicare Beneficiaries

Abstract: Purpose To examine the utilization and cost of post-acute care following isolated distal radius fractures (DRF) among Medicare beneficiaries. Methods We examined utilization of post-acute care among Medicare beneficiaries who experienced an isolated DRF (n=38,479) during 2007 using 100% Medicare claims data. We analyzed the effect of patient factors on hospital admission following DRF and the receipt of post-acute care delivered by skilled nursing facilities (SNFs), inpatient rehabilitation facilities (IRFs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…Zhong et al 2015 found that the accessibility of post-acute care was higher among women, patients residing in urban areas, and patients of higher socioeconomic status. 42 Another study that examined 1.1 million discharges of Medicare patients aged ≥65 years found that patients who were referred to home health care at discharge were more likely to be older, female, live in an urban location, have lower income, have a longer length of stay, have higher illness severity scores, have a diagnosis of heart failure or sepsis, and be hospitalized in New England (vs the Pacific). 15 Hartman et al 2007 analyzed the 2002 Medicare home health care data and found that although the proportion of Medicare beneficiaries nationwide who lived in areas with few home health care agencies was relatively low, less than 1% of urban beneficiaries lived in ZIP codes with no or low use of home health care compared to more than 17% of the most rural beneficiaries.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Zhong et al 2015 found that the accessibility of post-acute care was higher among women, patients residing in urban areas, and patients of higher socioeconomic status. 42 Another study that examined 1.1 million discharges of Medicare patients aged ≥65 years found that patients who were referred to home health care at discharge were more likely to be older, female, live in an urban location, have lower income, have a longer length of stay, have higher illness severity scores, have a diagnosis of heart failure or sepsis, and be hospitalized in New England (vs the Pacific). 15 Hartman et al 2007 analyzed the 2002 Medicare home health care data and found that although the proportion of Medicare beneficiaries nationwide who lived in areas with few home health care agencies was relatively low, less than 1% of urban beneficiaries lived in ZIP codes with no or low use of home health care compared to more than 17% of the most rural beneficiaries.…”
Section: Discussionmentioning
confidence: 98%
“…The proportion female, median income, and urban/rural location of the county were all associated with availability of home health care in our study. Zhong et al 2015 found that the accessibility of post‐acute care was higher among women, patients residing in urban areas, and patients of higher socioeconomic status . Another study that examined 1.1 million discharges of Medicare patients aged ≥65 years found that patients who were referred to home health care at discharge were more likely to be older, female, live in an urban location, have lower income, have a longer length of stay, have higher illness severity scores, have a diagnosis of heart failure or sepsis, and be hospitalized in New England (vs the Pacific) .…”
Section: Discussionmentioning
confidence: 99%
“…They also found that patients of lower SES are less likely to use post–acute care that could potentially help with pain and disability and that those of lower SES may not have access to the same rehabilitation services. 37…”
Section: Resultsmentioning
confidence: 99%
“…They also found that patients of lower SES are less likely to use post-acute care that could potentially help with pain and disability and that those of lower SES may not have access to the same rehabilitation services. 37 Higher SES has also been found to be associated with greater use of postoperative therapy such as physical or occupational therapy that would presumably be associated with better patient outcomes. 34 A review of claims and regional data revealed that patients of high (OR, 1.57; 95% CI, 1.46-1.70) or medium (OR, 1.22; 95% CI, 1.12-1.32) SES were more likely to receive therapy compared with patients of lower SES.…”
Section: Incomementioning
confidence: 99%
“…Zhong et al 63 found that postacute care, including inpatient rehabilitation and skilled nursing facilities, accounted for 69% of the total cost of distal radius fracture care in Medicare patients. In addition, older patients, women, those with more comorbid conditions, those with higher socioeconomic status, and those living in urban environments used more postacute care.…”
Section: Physical Therapymentioning
confidence: 99%